Investigating Multicultural Education Phenomena in Minority and Public High Schools in Turkey: A multiple case study - Akinlar, Aylin; Dogan, Suleyman (ANI YAYINCILIK, 2017)
Purpose: Upon inspection of Turkish national programs, it is seen that today they incorporate more universal values and principles such as democracy and pluralism. In order to design systems and curricula for multicultural societies, it is of great importance to thoroughly understand the phenomenon of multicultural education in minority and public high schools in Turkey; since the number of qualitative studies conducted on this topic remains inadequate. The aim of this study is to investigate the perceptions and implementations of multicultural education among different participants from a minority high school and two public high schools in Istanbul, Turkey. Method: The methodology of this study was grounded in the principles of qualitative study. The maximum variation sampling method of purposive sampling methods was used. The data for the study was collected via triangulation during the 2014-2015 academic years. Particularly, an interview study method was employed. Findings: Participants indicated that multicultural education could contribute to more opportunities and equal education rights for all. Participants also expressed that multicultural education was required by different people from various cultures to live with equal rights and for society to be a more fair and democratic ground for people from all walks of life. Implications for Research and Practice: The research demonstrates that teachers need to receive a comprehensive training on multicultural education. As participants reported, teachers should use examples and content from a variety of cultures and groups to show key concepts, principles, generalizations, and theories in their subject area or discipline. (C) 2017 Ani Publishing Ltd. All rights reserved
Keywords: multicultural education; qualitative multiple case study; Education & Educational Research